Association between circulating tumor DNA burden and disease burden in patients with ALK‐positive lung cancer. Issue 20 (5th August 2020) - Zhang, Eric W.; Dagogo‐Jack, Ibiayi; Kuo, Anderson; Rooney, Marguerite M.; Shaw, Alice T.; Digumarthy, Subba R.
Abstract : Background: Plasma genotyping is an emerging approach for the identification of genetic alterations mediating resistance to anaplastic lymphoma kinase (ALK)–targeted therapy. The authors reviewed plasma genotyping and imaging findings to assess the correlation between circulating tumor DNA (ctDNA) burden and disease burden in patients with ALK‐positive lung cancer. Methods: The authors analyzed 97 plasma specimens from 75 patients with ALK‐positive lung cancer to identify ALK and non‐ ALK alterations. Disease burden was estimated by tabulating lesions per organ and calculating lesion diameters, areas, and volumes. Disease burden was correlated with the allelic frequency (AF) of plasma alterations. Results: The mean interval between plasma collection and imaging was 8 days. ctDNA was detected in approximately 85% of plasma specimens. An ALK fusion and ALK mutation were detected in 79% and 76%, respectively, of plasma specimens. Using the maximum plasma alteration AF and maximum ALK alteration AF as independent surrogates of ctDNA burden, a higher disease burden measurement on imaging was found to be associated with higher ctDNA burden. Total body and extrathoracic tumor volume but not intrathoracic tumor volume correlated with ctDNA burden. Of all the disease sites assessed, the ctDNA burden correlated most with involvement of the liver, bones, and adrenal glands. Despite being the defining alteration in ALK‐positive lung cancer, isolated plasma ALK fusion AF did not perform as well as the maximum plasma alteration AF or maximum ALK alteration AF for correlating tumor burden. Conclusions: In patients with ALK‐positive lung cancer, the maximum plasma alteration AF and maximum ALK alteration AF correlate with the extrathoracic burden of disease and are more predictive of tumor burden compared with the ALK fusion AF alone. Lay Summary: Analysis of genetic material shed from cancer cells into the circulation offers insights into the molecular composition of tumors. The circulating tumor DNA (ctDNA) varies over time and across individuals and is impacted by the distribution of disease. Herein, the authors estimated tumor burden on imaging and correlated it with ctDNA by calculating the maximum allelic frequency. The current study findings demonstrated that the greatest correlation exists between extrathoracic, extracranial tumor burden (particularly involvement of the liver, adrenal glands, or bones) and ctDNA burden, suggesting a biological basis for the interpatient and temporal intrapatient differences in ctDNA yield that have been described in previous studies. Abstract : Plasma genotyping of circulating tumor DNA (ctDNA) has emerged as a clinical tool for the identification of underlying driver mutations and resistance mechanisms in patients with lung cancer. In patients with advanced, ALK‐positive lung cancer, plasma genotyping yields higher quantities of ctDNA in those patients found to have a high extrathoracic disease burden on imaging, particularly within the setting of hepatic, adrenal, and bone metastases.